Preparation, Standardization and Anti-plasmodial Efficacy of Novel Malaria Nosodes - Suri, Mansi; Walter, Neha Sylvia; Katnoria, Sapna; Gorki, Varun; Manchanda, Raj Kumar; Khurana, Anil; Nayak, Debadatta; Bagai, Upma; Kaur, Sukhbir (Homeopathy, 2021)
Background Resistance to artemisinin and its partner drugs has threatened the sustainability of continuing the global efforts to curb malaria, which urges the need to look for newer therapies to control the disease without any adverse side effects. In the present study, novel homeopathic nosodes were prepared from Plasmodium falciparum and also assessed for their in vitro and in vivo anti-plasmodial activity.Methods Three nosodes were prepared from P. falciparum (chloroquine [CQ]-sensitive [3D7] and CQ-resistant [RKL-9] strains) as per the Homeopathic Pharmacopoeia of India, viz. cell-free parasite nosode, infected RBCs nosode, mixture nosode. In vitro anti-malarial activity was assessed by schizont maturation inhibition assay. The in vitro cytotoxicity was evaluated by MTT assay. Knight and Peter's method was used to determine in vivo suppressive activity. Mice were inoculated with P. berghei-infected erythrocytes on day 1 and treatment was initiated on the same day. Biochemical, cytokine and histopathological analyses were carried out using standard methods.Results In vitro: the nosodes exhibited considerable activity against P. falciparum with maximum 71.42% (3D7) and 68.57% (RKL-9) inhibition by mixture nosode followed by cell-free parasite nosode (62.85% 3D7 and 60% RKL-9) and infected RBCs nosode (60.61% 3D7 and 57.14% RKL-9). The nosodes were non-toxic to RAW macrophage cell line with >70% cell viability. In vivo: Considerable suppressive efficacy was observed in mixture nosode-treated mice, with 0.005 ± 0.001% parasitemia on day 35. Levels of liver and kidney function biomarkers were within the normal range in the mixture nosode-treated groups. Cytokine analysis revealed increased levels of IL-4 and IL-10, whilst a decline in IL-17 and IFN-γ was evident in the mixture nosode-treated mice.Conclusion The mixture nosode exhibited promising anti-malarial activity against P. falciparum and P. berghei. Biochemical and histopathological studies also highlighted the safety of the nosode for the rodent host. The study provides valuable insight into a novel medicament that has potential for use in the treatment of malaria.
Keywords: malaria; homeopathy; nosodes; Plasmodium; anti-malarial activity